Antimicrobial Screening of Phytochemicals Extracted Form Selected Medicinal Plants - Ram Bhajan Kumawat, Dr. Priti Kaushik, Dr. Geeta Meena (International Journal of Advanced Science and Technology, 2020)
Human being has used the plants and their various products from ancient time because their products cause fewer side effects. In the present study we evaluated twotraditional Indian medicinal plants they are shown ethanomedicinal andpharmacological properties. Several researchers in Indiahave been assed different activities of these two medicinal plantsare,Delonix regiaand Citrullus colocynthis. They shows many medicinal and pharmacological activitieslike, Anti-inflammatory, antifungal, antibacterial, antioxidant, analgesic or anti-proliferative and antifertility etc. Delonixregia and Citrulluscolocynthis usedin different parts of India around the world.